ON PRAGMATIC IMPLICATURE: POLITICAL LANGUAGES IN 2018 ELECTIONS IN ACEH - Batubara, Muhammad Hasyimsyah (International Journal of Humanity Studies (IJHS), 2020)
Indonesian politics in the reform era provided a broad space for anyone to participate in competing for the executive and legislative seats. This impacts on how candidates or partners are able to sell themselves to the community in order to get positive sentiment in the eyes of the community. One way politicians make votes is how they use language as a function of communication to boost popularity and electability. To conduct political communication, politicians generally use advertising media, especially outdoor promotional media to propagate people. From the author's observation, the language used in the outdoor promotion media, almost allÂ  regional election 2018 candidates in Aceh (Pidie Jaya, South Aceh, and Subulussalam) used language in the realm of pragmatic studies. Text in outdoor advertising media tends to use the meaning of implicature. Speech acts in outdoor advertising in the Pidie Jaya area are dominated by assertive/collaborative illocutionary utterances. There were 5 assertions of assertive illocutionary speech, 3 directive illocutionary speech acts, and one outdoor advertisement containing a mixture of assertive ilocution and direct illocutionary. In the South Aceh area 9 assertive ilocutionary utterances were found, and direct illocutionary speech acts were used for 5 utterances. Whereas in the Subulussalam area there are 5 utterances in assertive/collaborative illocutionary and directive utterances. A good understanding of implicature is learning for us in capturing the meaning of speech messages or speech acts of candidates for regional elections, which in the end are able to make smart political choices from the speeches and discourses of politicians that we consider relevant to the situation, of course also from track record support candidate so far. In the end we are not trapped like the statement delivered by Charles de Gaulle, President of the French Republic "Politicians never believe in their own words, they are actually surprised when people believe it". And the chosen one "Truly the best of men for thee to employ is the (man) who is strong and trustworthy." (QS. Al-Qashas: 26).